DNA/RNA heteroduplex technology with cationic oligopeptide reduces class-related adverse effects of nucleic acid drugs - Masahiro Ohara; Tetsuya Nagata; Rintaro Iwata Hara; Kie Yoshida-Tanaka; Nozomi Toide; Kazunori Takagi; Kazuki Sato; Tomoya Takenaka; Masanori Nakakariya; Kenichi Miyata; Yusuke Maeda; Kazuko Toh; et al. (Elsevier, 2024)
Antisense oligonucleotides (ASOs) are a therapeutic modality for incurable diseases. However, systemic injection of gapmer-type ASOs causes class-related toxicities, including prolongation of activated partial thromboplastin time (aPTT) and thrombocytopenia. We previously reported that cholesterol-conjugated DNA/RNA heteroduplex oligonucleotides (Chol-HDOs) exhibit significantly enhanced gene-silencing effects compared to ASOs, even in the central nervous system, by crossing the blood-brain barrier. In the present study, we initially evaluated the effect of the HDO structure on class-related toxicities. The HDO structure ameliorated the class-related toxicities associated with ASOs, but they remained to some extent. As a further antidote, we have developed artificial cationic oligopeptides, L-2,4-diaminobutanoic acid oligomers (DabOs), which bind to the phosphates in the major groove of the A-type double-helical structure of HDOs. The DabO/Chol-HDO complex showed significantly improved aPTT prolongation and thrombocytopenia in mice while maintaining gene-silencing efficacy. Moreover, the conjugation with DabOs effectively prevented cerebral infarction, a condition frequently observed in mice intravenously injected with high-dose Chol-HDO. These approaches, combining HDO technology with DabOs, offer distinct advantages over conventional strategies in reducing toxicities. Consequently, the DabO/HDO complex represents a promising platform for overcoming the class-related toxicities associated with therapeutic ASOs.